Zearalenone nephrotoxicity: DNA fragmentation, apoptotic gene expression and oxidative stress protected by Lactobacillus plantarum MON03. (February 2020) - Ben Salah-Abbès, Jalila; Belgacem, Hela; Ezzdini, Khawla; Abdel-Wahhab, Mosaad A.; Abbès, Samir
Abstract: The present study was conducted to determine the abilities of the living Lactobacillus plantarum MON03 cells to degrade Zearalenone (ZEN) in liquid medium, and to elucidate the preventive effect in ZEN-contaminated balb/c mice showing kidney damage. The DNA fragmentation, Bcl-2 and Bax gene expression, caspase-3 activity, mRNA level of inflammation-regulating cytokines and histology of kidney tissues were examined. Female Balb/c mice were divided into four groups (10/group) and treated daily for 2 wk by oral gavage with lactic acid bacteria ( L. plantarum MON03) 2 × 10 9 CFU/L, 2 mg/kg only, ZEN (40 mg/kg BW) only, ZEN (40 mg/kg BW) + lactic acid bacteria ( L. plantarum MON03, 2 × 10 9 CFU/L, 2 mg/kg). Control group received vehicle. At the end of experiment, the kidney was collected for the determination of DNA fragmentation, Bcl-2 and Bax gene expression, caspase-3 activity, Malondialdehyde (MDA), and glutathione peroxidase (GSH-Px) content, as well as for any alterations in expression of total antioxidant activity (TAC) and mRNA levels of inflammation-regulating cytokines (e.g., IL-10, IL-6, TNF-alpha ). The results indicated that, kidney cells exposure to ZEN led to increased caspase-3 activity, MDA, and IL-10, IL-6, TNF-alpha and Bax mRNA levels, but decreased TAC content and down-regulated expression of GSH-Px and CAT and Bcl- 2 mRNA. Co-treatment with ZEN plus LP suppressed the levels of DNA fragmentation; normalized kidney MDA and increased CAT levels, up-regulated expression of GSH-Px and CAT, and normalized mRNA levels of the analyzed cytokines. It's concluded that ZEN might have toxic effects in kidney. Further, it can be seen that use of LP induced protective effects against the oxidative stress and kidney toxicity of ZEN in part through adhesion (and so likely diminished bioavailability). Highlights: Zearalenone increases DNA damage, Bcl-2 and decrease caspase-3; 9 and Bax mRNA levels. Lactobacillus plantarum MON03 protects against Zearalenone genotoxicity in kidney. Lactobacillus plantarum MON03 was safe and can be candidate in the ZEN detoxification.